The tadpole of Pleurodema cordobae Valetti, Salas & Martino, 2009 (Anura: Leiuperidae) from Córdoba, Argentina - Otero, Manuel A.; Grenat, Pablo R.; Valetti, Julian A.; Salas, Nancy E.; Martino, Adolfo L. (Zootaxa, 2013)
The frog genus Pleurodema Tschudi, 1838 is distributed from Panama throughout South America to southern Chile and Argentina and currently is represented by 15 species, of which 10 have been recorded in Argentina (Faivovich et al. 2012). Recently, Valetti et al. (2009) re-described the tetraploid species P. kriegi and described a related cryptic species, the octoploid Pleurodema cordobae. These species are endemic of the Sierra Grande of Córdoba (Ferraro & Casagranda 2009; Valetti et al. 2009; Valetti et al. 2011) and together with the tetraploid P. bibrioni comprise a clade of polyploid cryptic species within the genus (Faivovich et al. 2012). The external morphology has been described for the tadpoles of P. bibrioni and P. kriegi by Kolenc et al. (2009), but the tadpole of P. cordobae remains undescribed. The aim of this work is to describe the larval external morphology and oral disc of new species P. cordobae.